2004
DOI: 10.4141/p03-050
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency characteristics of commercial potato cultivars

Abstract: . 2004. Nitrogen use efficiency characteristics of commercial potato cultivars. Can. J. Plant Sci. 84: 589-598. One approach for reducing the contribution of potato (Solanum tuberosum L.) production to nitrate contamination of groundwater is to develop cultivars which utilize N more efficiently. In this study, variation in N use efficiency (NUE; dry matter production per unit crop N supply) characteristics of 20 commercial potato cultivars of North American and European origin were evaluated in 2 yr. Cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 23 publications
12
98
2
3
Order By: Relevance
“…Nos países da Europa e nos Estados Unidos, a dose de N recomendada varia de 70 a 330 kg ha -1 , com ciclo de cultivo em torno de cinco meses (Kolbe & Beckmann, 1997), e, no Canadá, de 165 a 215 kg ha -1 (Zebarth et al, 2004). No Brasil, é possível encontrar recomendações de fertilização variando de 60 a 250 kg ha -1 de N (Fontes, 1999).…”
Section: Resultsunclassified
“…Nos países da Europa e nos Estados Unidos, a dose de N recomendada varia de 70 a 330 kg ha -1 , com ciclo de cultivo em torno de cinco meses (Kolbe & Beckmann, 1997), e, no Canadá, de 165 a 215 kg ha -1 (Zebarth et al, 2004). No Brasil, é possível encontrar recomendações de fertilização variando de 60 a 250 kg ha -1 de N (Fontes, 1999).…”
Section: Resultsunclassified
“…3 was generally low, at what might be considered to be background levels. For example Zebarth et al (2004a) found that under N limited conditions, commercial potato cultivars reduced soil NO 3 -N concentrations to about 4 mg N kg -1 soil. This is equivalent to a soil NO 3 -N content of 12 kg N ha -1 for the 0-to 30-cm depth, assuming a soil bulk density of 1.0 Mg m -3 , and is similar to the average soil NO 3 -N content of 14 kg N ha -1 measured at harvest in exp.…”
Section: Discussionmentioning
confidence: 99%
“…Plant dry matter and N accumulation were determined as described by . Harvest index (HI) was calculated as tuber dry matter divided by total plant dry matter, and N harvest index (NHI) as tuber N accumulation divided by total plant N accumulation; both were expressed as a percentage (Zebarth et al 2004a). The statistical analysis combined the data over years with years as a random effect, fertility treatments as main plots and cultivars as sub-plots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry matter production of potato varies with climate, variety and management (Geremew et al, 2007), but has a linear increase with N supply up to certain levels (Zebarth et al, 2004), which improves its tuber quality (Roinila et al, 2003). Additionally, the total dry matter of potato accumulated by photosynthesis is utilized in different parts of the plant according to its development stage (Singh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%